Decarbonizing Growth: The Role of Human Capital Development and Innovation in Malaysia’s Pursuit of SDG 13 - Yun, Wong Sing; Ridzuan, Abdul Rahim; Izadin , Ahmad Al Izham; Wudil, Adamu Ahmed; Ruiqi, Zhang; Ann, Teo Sue (International Journal of Energy Economics and Policy, 2025)
This study investigates the impact of human capital development and technological innovation on environmental sustainability in Malaysia, as part of the Malaysian commitment to Sustainable Development Goal 13 (Climate Action). Using Autoregressive Distributed Lag (ARDL) model and time series data covering the period 1990-2022, the analysis explores the dynamic relationship between CO2 emissions and major macroeconomic variables, namely economic growth, energy consumption, technological innovation, trade openness, foreign direct investment (FDI), quality of governance, education, and GINI coefficient. The empirical findings reveals that technological innovation and human capital development significantly contribute to long-run decline in CO2 emission, hence emphasis their role in ensuring a sustainable low-carbon economy. On the other hand, FDI correlates with higher emissions, which gives relevance to pollution haven hypothesis in the Malaysian case. The study emphasis the need to invest in green technology, incorporate sustainability in the education system and tightening environmental standards in the foreign investments. Such policy steps are necessary to ensure that economic progress is no longer linked to environmental degradation and accelerate Malaysia’s transition towards a climate-resilient future.